Examining the impact of zakah and Islamic finance on national economic growth - Pebruary, Silviana; Isnaini Hani'ah (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study aims to analyze the effect of Islamic financial instruments, including social funds zakah, infak, and sadaqah (ZIS), Islamic financing, Sharia stocks, and corporate sukuk, on economic growth.Methodology – This study uses monthly data from 2013 to 2022 to examine the relationship between ZIS distribution, Islamic bank financing, Islamic stock capitalization, corporate sukuk issuance, and economic growth proxied by the production industry index (IPI). The Vector Error Correction Model (VECM) was utilized.Findings – According to the short-term estimation results, sukuk significantly hinders economic growth, whereas only the ZIS variable has a positive and significant impact. Long-term economic growth is positively impacted by the ZIS and Islamic financing variables, negatively impacted by sukuk, and not significantly impacted by Sharia stock. The Impulse Response Function and Variance Decomposition analysis results also demonstrate that the variables of the Islamic financial sector have a shock effect on Indonesia's economic growth, with ZIS funds making up the majority of the contribution and Sharia stocks the least.Implications – This study will help policymakers, industry, and academia accelerate the Islamic finance sector in Indonesia and strengthen its role in supporting and advancing Indonesia's economic recovery.Originality – Islamic finance, commonly known as Islamic banking–extends beyond Indonesian banks. Non-bank Islamic institutions, including capital markets and social finance, play a vital role in optimizing Islamic financial instruments for national economic growth.